Culturally relevant informal STEM learning for underserved students: effects of repeated exposure to the engineering design process - Barajas-Salazar, Bianca E.; Almeida, Melissa; Aguirre-Muñoz, Zenaida; Viveros, Maribel (Frontiers in Education, 2025)
IntroductionThis study investigates the impact of repeated exposure to the Engineering Design Process (EDP) through culturally responsive STEM lessons, delivered in an informal science learning (ISL) setting to middle school students from underserved communities in California’s Central Valley.MethodsA mixed-methods approach was employed, combining qualitative analysis of student journals and survey responses with quantitative analysis of pre- and post-survey data. The study focused on students’ STEM identity, self-efficacy, and perceptions of engineering knowledge.ResultsQualitative findings highlighted key themes of problem-solving and understanding the EDP, demonstrating that students engaged deeply with the process. Quantitative results indicated significant improvements in students’ STEM identity, self-efficacy, and perceptions of engineering knowledge following repeated exposure to the EDP.DiscussionThese findings suggest that embedding the EDP within culturally relevant, hands-on ISL activities can effectively enhance students’ engagement with STEM subjects, foster stronger STEM identities, and address educational inequities.